HISTORICAL-PHILOSOPHICAL COMPONENTS OF POLICY AND MO-RALITY RELATIONS - Dmytro V. Usov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2014)
The aim. To analyze comprehensively the policy as a way of human being, as well as the important today’s criteria of legitimacy of the government and the nature of political morality through a consistent reconstruction of the relations between morality and politics in the contemporary and classic historical and philosophical discourses. Methodology. The methods of historical reconstruction, hermeneutic, social and transcendental ones, which allowed to involve actively into understanding the important problems of modern life, conceptual apparatus of political and moral philosophy and to explore the relationships between politics and morality through the idea of social agreement, justice and freedom are used for coherent and consistent understanding of the measurements and definitions of relations policy and morality. Scientific novelty. The used in the article methodological principles made it possible to create actual for today (especially for controversial burdened by totalitarian past and uncertain future of a controversial, local realities) version of political ethics. It is proved that the development of moral and ethical principles, their consistent adherence by not only politicians, but by all the citizens are able to hinder the pragmatic interests of statesmen, who, under cover of the idea of the common good, protect primarily not the public but narrow corporate interests. A true freedom and justice based on the relationship of rights and duties, respect for them, which is more significant than conventional or compulsory recognition of them. Not only classic but also modern philosophical arguments for the combination of morality, ethics and politics were reconstructed. The thoughts of E. Tuhendhat about the nature of morality as a special regulatory system, and the basic principles of justification of moral standards in a modern philosophy were analyzed. It is shown that the landscape of contemporary crisis of social being, moral principles appear both as formal and procedurally - material ones, but the necessary for politicians mental attitude not only to their close, but also to other people requires the willingness to be honest and open. Conclusions. The understanding of the ways of combining the morality and politics through the achievements of a compromise of completive views and life strategies is essential for the development of real, but not apparent "legal state" in which the ruling authority represents not the interests of citizens, but only their own interests and goods. Concerning the public discourse of social agreement, it goes about the need for compromise and consideration of individual life plans, and the problem of legitimacy of power and necessary for the operation of universal principles of sense of justice and trust.